A COMPARATIVE STUDY OF THE LEGAL FRAMEWORKS FACILITATING INDIGENOUS LAND MANAGEMENT IN POSTCOLONIAL SOCIETIES: INDIGENOUS AUSTRALIA AND INDONESIAN ADAT LAW - Boag, Carly May (Faculty of Law, Universitas Brawijaya, 2016)
Indigenous Land Management (ILM) encompasses traditional philosophies and practices of Indigenous people with contemporary scientific techniques to help improve the management and conservation of ecosystems. An effective legal framework for ILM promotes environmental justice by